Konseling Behavioral dengan Teknik Modeling untuk Meningkatkan Self Exhibition - Jayanthi, Kadek Karmila; Dantes, Nyoman; Gading, I Ketut (Universitas Pendidikan Ganesha, 2019)
This study aims to study the effectiveness of counseling behavior with modeling techniques to improve Self Exhibition. The design of this study was experimental research with a pretest-posttest-control group research design. The sample of this study was students of class VII.4 and class VII.1 The Undiksha Laboratory Middle School was taken randomly from 4 classes of population members. Self Exhibition data collection in this study used the Self Exhibition questionnaire. Hypothesis testing is done using the t test. From the T test performed it was obtained at 9,808 with significance of <0.001. This was discussed by counseling behavioral engineering modeling with effective study study arrangements to improve junior high school students' self exhibitions.Keywords: Behavioral Counseling, modeling, self exhibition